Surface-Enhanced Raman Scattering of Bacteria in Microwells Constructed from Silver Nanoparticles - Mustafa Çulha; M. Müge Yazıcı; Mehmet Kahraman; Fikrettin Şahin; Sesin Kocagöz (Journal of Nanotechnology)
Whole bacterial cell characterization is critically important for fast bacterial identification. Surface-enhanced Raman scattering (SERS) is proven to be powerful technique to serve such a goal. In this study, the characterization of whole bacterial cells in the microwells constructed from colloidal silver nanoparticles (AgNPs) with “convective-assembly” method is reported. The proper size of the microwells for the model bacteria, Escherichia coli and Staphylococcus cohnii, is determined to be 1.2 μm from their electron microscopy images. A minimum dilution factor of 20 is necessary for the bacterial samples collected from growth media to diminish the bacterial aggregation to place the bacterial cells into the microwells. The constructed microwell structures are tested for their bacterial SERS performance and compared to the SERS spectra obtained from the samples prepared with a simple mixing of bacteria and AgNPs for the same bacteria. The results indicate that microwell structures not only improve the spectral quality but also increase the reproducibility of the SERS spectra.